2022
DOI: 10.3390/md20120780
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Optimization of Culture Conditions for Aurantiochytrium sp. SC145 Isolated from Sand Cay (Son Ca) Island, Vietnam, and Antioxidative and Neuroprotective Activities of Its Polyunsaturated Fatty Acid Mixture

Abstract: Aurantiochytrium is a heterotrophic marine microalga that has potential industrial applications. The main objectives of this study were to isolate an Aurantiochytrium strain from Sand Cay (Son Ca) Island, Vietnam, optimize its culture conditions, determine its nutritional composition, extract polyunsaturated fatty acids (PUFAs) in the free (FFA) and the alkyl ester (FAAE) forms, and evaluate the antioxidation and neuroprotection properties of the PUFAs. Aurantiochytrium sp. SC145 can be grown stably under labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Superior meat quality is characterized by taste, texture, and nutritional attributes, often warranting premium prices due to consumer preferences (Hathwar et al 2012 ). As such, improving meat quality, and particularly its nutritional content, can substantially advance the profitability of ruminant production (Delgado-Pertíñez et al 2021 ).…”
Section: Influence Of Dietary Microalgae Supplementation On Ruminant ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Superior meat quality is characterized by taste, texture, and nutritional attributes, often warranting premium prices due to consumer preferences (Hathwar et al 2012 ). As such, improving meat quality, and particularly its nutritional content, can substantially advance the profitability of ruminant production (Delgado-Pertíñez et al 2021 ).…”
Section: Influence Of Dietary Microalgae Supplementation On Ruminant ...mentioning
confidence: 99%
“…Nannochloropsis spp., on the other hand, can accumulate high levels of an omega-3 very long chain fatty acid termed eicosapentaenoic acid (EPA) under stressful conditions (Ma et al 2014;Rebolloso-Fuentes et al 2001), while Isochrysis galbana and Schizochytrium spp. can produce high amounts of a similar fatty acid termed docosahexaenoic acid (DHA) (Hien et al 2022;Mohy El-Din 2019;Xu et al 2021). Both EPA and DHA can enhance animal health and the nutritional value of animal products (Barta et al 2021).…”
Section: Representative Microalga Species Used As Ruminant Feed Addit...mentioning
confidence: 99%
“…Existing research has demonstrated that thraustochytrid PUFAs or intracellular lipid extracts possess anti-inflammatory (Takahashi et al, 2019), antioxidant (Hien et al, 2022;Kalidasan et al, 2022;Kaliyamoorthy et al, 2023), neuroprotective (Hien et al, 2022) and anticancer properties (Shakeri et al, 2017;Kalidasan et al, 2022), highlighting their significant medicinal value (Table 3). Dietary supplementation with DHA has been proven to effectively elevate plasma total DHA levels (reaching 65 mM) (Mayer et al, 2003).…”
Section: Harnessing Thraustochytrids For Nutraceutical and Functional...mentioning
confidence: 99%
“…In addition, Thraustochytrium spp. has been reported to produce carotenoids (β‐carotene, echinenone, canthaxanthin, phoenicoxanthin, and astaxanthin) (Carmona et al, 2003; Hien et al, 2022; Yamaoka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%